Impact of Different Topology on the Performance of IPSec VPN Multimedia Using CLSA - Sari, Linna Oktaviana; Batubara, Aldi Kurniawan (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2018)
Due to multimedia application, network communication are expected to support multimedia traffic such as voice, video streaming and real time chat with a variety of Quality of Service (QoS) requirements. To support multimedia communications, it is desirable to use a network that meets QoS Parameter requirements. To deal with these challenges. In this study, VPN was designed with IPSec Tunneling. In designing VPN, the CLSA method is used. The network is composed of different topologies and uses OSPF as the routing protocol. Then multimedia traffic is passed on VPN networks to see the impact of different topologies on performance.The result show that theQuality of Service (QOS)in VPNobtained areaccording to ITU-T G.107 10 06/2015. The comparison of the average delay between the mesh and the star topology shows that the average delay in the mesh topology is 23% less than the starfor multimedia traffic. The comparison of the through put between the mesh topology and the star shows that the average throughputin the mesh topology is 68.8% betterthan the star for multimedia traffic. The comparison of the jitterbetween the mesh topology and the star shows that the average jitter in the star topology is 6%shorterthan the mesh for multimedia traffic.